Utilization of waste cooking oil into aromatherapy candles - Ine Suharyani; Wildan Akmal Nuriansyah; Silvia Baetul Ulfa; Sopi Siti Sopiah; Wulan Rabbani Akbar; Dwi Novikasari Naros; Julia Savira; Alifia Hidayati Mursalim; Muhammad Raihan Aranda Ghazany S; Siti Hajar (Community Empowerment, 2023)
Home industries in Cipeujeuh Kulon Village produce a significant quantity of used cooking oil to process the food they manufacture. The objective of this service program is to diminish the recurrent use of discarded cooking oil, decrease consumption, and minimize the amount of culinary waste by utilizing used cooking oil as a fundamental ingredient in crafting aromatherapy candles. The employed methods encompass socialization and hands-on practice. The outcomes of this initiative reveal an enhanced public comprehension, encouraging individuals to abstain from consuming used cooking oil while promoting its utilization in crafting aromatherapy candles. Furthermore, participants demonstrate the ability to independently produce aromatherapy candles using used cooking oil.